A cross‐scale analysis to understand and quantify the effects of photosynthetic enhancement on crop growth and yield across environments. (20th October 2022) - Wu, Alex; Brider, Jason; Busch, Florian A.; Chen, Min; Chenu, Karine; Clarke, Victoria C.; Collins, Brian; Ermakova, Maria; Evans, John R.; Farquhar, Graham D.; Forster, Britta; Furbank, Robert T.; et al.
Abstract: Photosynthetic manipulation provides new opportunities for enhancing crop yield. However, understanding and quantifying the importance of individual and multiple manipulations on the seasonal biomass growth and yield performance of target crops across variable production environments is limited. Using a state‐of‐the‐art cross‐scale model in the APSIM platform we predicted the impact of altering photosynthesis on the enzyme‐limited ( A c ) and electron transport‐limited ( A j ) rates, seasonal dynamics in canopy photosynthesis, biomass growth, and yield formation via large multiyear‐by‐location crop growth simulations. A broad list of promising strategies to improve photosynthesis for C3 wheat and C4 sorghum were simulated. In the top decile of seasonal outcomes, yield gains were predicted to be modest, ranging between 0% and 8%, depending on the manipulation and crop type. We report how photosynthetic enhancement can affect the timing and severity of water and nitrogen stress on the growing crop, resulting in nonintuitive seasonal crop dynamics and yield outcomes. We predicted that strategies enhancing A c alone generate more consistent but smaller yield gains across all water and nitrogen environments, A j enhancement alone generates larger gains but is undesirable in more marginal environments. Large increases in both A c and A j generate the highest gains across all environments. Yield outcomes of the tested manipulation strategies were predicted and compared for realistic Australian wheat and sorghum production. This study uniquely unpacks complex cross‐scale interactions between photosynthesis and seasonal crop dynamics and improves understanding and quantification of the potential impact of photosynthesis traits (or lack of it) for crop improvement research. Summary Statement: Grain yield per area information of photosynthetically manipulated crop plants is limited. Cross‐scale modelling predicted how growth dynamics of wheat and sorghum crops can be affected and quantified various manipulation impacts on grain yield in multiple environments for crop improvement research.